How to pack for the end of the world - Falkoff, Michelle (HarperTeen, 2022)
After her parents become increasingly worried about her intense obsession about the end of the world, they send Amina to Gardner Academy where she meets a group of students with similar fears. Together, they form the Eucalyptus Society where they test each others survival skills. But soon the group is targeted by a mysterious stranger who is anonymously and publicly humiliating them. As secrets are revealed, Amina and her new friends begin to wonder if they can really trust each other.